Emergency response and hazardous chemicl management : principles and practices - Strong, Clyde B. (St. Lucie Press, 1997)
Introduction:workplace hazards durint chemical emergency response actions.--Chemistry and properties of hazardous substances.--Toxicology principles.--Monitoring and detecting hazardous chemicalss.--Industrial higuiene issues.--medical surveillance programs.--Respiratory protection: principles and practices.--Chemical protective clothing.--Chemical decontamination: principles and practices.--Safety in confoned spaces.--Standard operating safety procedures.--Hazardous chemicals spill containment.--Patching and capping of leaking containers.--Techniques for spill stabilization.--Preparing hazardous waste for transportation: DOT hazardous waste transportation requeriments.--Incident analysis and initial response.--Incident command system